Racial disparities in urine drug screening among seizure patients in the emergency department - Gloria Ortiz-Guerrero; Maggie Logan; Utku Uysal; Patrick Landazuri; Lakeshia Jackson; Carol M. Ulloa (PLoS ONE, 2025)
Background The potential for racial disparity using urine drug screening (UDS) in patients with seizures is sparsely reported. This study aims to determine racial and ethnic disparities when ordering UDS in patients with suspected seizures in the emergency department (ED). Methods In this retrospective study, we identified patients over the age of 18 with suspected seizures who presented to the ED at the University of Kansas Medical Center between October 2017 and October 2020. Data encompassed demographic, clinical, electrographic, and UDS information from the electronic medical records (EMR). Data were compared between Black and White patients, as well as between Hispanic and non-Hispanic patients. We used the Chi-square test to assess differences in UDS testing based on patient race and ethnicity. Results A total of 2945 patients were identified. Among these, 1750 (59%) were White and 821 (28%) were Black patients. Of these patients, 612 (20.8%) underwent UDS in the ED. Black patients had UDS performed more frequently compared to White patients (p = 0.046). Additionally, the positivity rate for UDS was higher among Black patients than White patients (p = 0.019). UDS testing did not differ by ethnicity (p = 0.164). Amphetamine positivity was higher among White patients; however, the positivity rates of other drugs did not differ by race and ethnicity. Black patients were more often admitted to the neurology intensive care unit. No differences in discharge rates or EEG testing were noted across race or ethnicity. Conclusion Increased UDS testing was seen in Black patients compared to White patients in our single-institution cohort, warranting further research into the underlying causes of this disparity.